PERSEPSI MAHASISWA MENGENAI MONEY ETHICS TERHADAP TAX EVASION DENGAN GENDER DAN MORALITY SEBAGAI VARIABEL MODERASI - Putri Ramawati, 15.05.52.0090; Meita Oktaviani, Rachmawati (Students' Journal of Accounting and Banking, 2019)
Ethics with gender and moral as a moderating variable on tax evasion. The population in this study were accounting students who had taken taxation courses. The sample technique used is based on purposive sampling by determining the criteria of respondents before being used as research samples. Data analysis techniques are performed by regression using the Moderate Regression Analysis (MRA). The results showed that the perception of accounting students regarding money ethics had a significant positive effect on tax evasion. The role of gender as a moderating variable can weaken the positive relationship of money ethics towards tax evasion. In addition, the same results are also shown by morality as moderation variables which can weaken the positive relationship of money ethics with tax evasion.